PENGARUH KINERJA KEUANGAN TERHADAP HARGA SAHAM PADA PERUSAHAAN BUMN (NON-BANK) YANG TERDAFTAR DI BURSA EFEK INDONESIA - Aldiansyah Cahya Putra; Saryadi Saryadi; Wahyu Hidayat (Universitas Diponegoro, 2014)
Purchasing of stocks is one of the alternate investation that is interesting for the investors, because there are two returns that will be expected. The first is dividend, Second is Capital Gains. The benefit ability of high companies can also increase the stock prices. Ratio - the ratio of liquidity such as Current Ratio (CR), profitability such as Return on Investment (ROI) and Return on Equity (ROE), and the ratio of activities such as Total Asset Turnover (TATO) can affect the company's stock price.This research aims to determine the effect of the ratio of Current Ratio (CR), Return on Investment (ROI), Return on Equity (ROE) and Total Asset Turnover (TATO) on Stock Prices. Population as well as the sample in this research is a state-owned company financial / BUMN data listed in the Indonesia Stock Exchange in 2010 and 2012 and it is obtained 13 state-owned companies listed on the Indonesia Stock Exchange. Data collection in this research is done by downloading the Annual Report the companies through the website www.idx.co.id . In the data analysis uses the classical assumption test, simple linear regression and multiple regression test with SPSS program.The results show variable Current Ratio (CR) has an influence on the stock price of 0.220,but not significant. Variable Return on Investment (ROI) has an influence on the stock price of 0.360, but not significant. Variable Return on Equity (ROE) have an influence on the stock price of 0.655. Variable Total Asset Turnover (TATO) has an influence on the stock price of 0,439. Variable Current Ratio (CR), Return on Investment (ROI), Return on Equity (ROE) and Total Asset Turnover (TATO) have a positive influence simultaneously to the stock prices that is equal to 77,6%. This suggests that all of Current Ratio (CR), Return on Investment (ROI), Return on Equity (ROE) and Total Asset Turnover (TATO) 2010-2012 State Owned Company can affect the stock prices.